The relation of price of antiretroviral drugs and foreign assistance with coverage of HIV treatment in Africa: retrospective study. (18th November 2010) - Bendavid, Eran; Leroux, Eric; Bhattacharya, Jay; Smith, Nicole; Miller, Grant
Abstract : Objective To determine the association of reductions in price of antiretroviral drugs and foreign assistance for HIV with coverage of antiretroviral treatment. Design Retrospective study. Setting Africa. Participants 13 African countries, 2003-8. Main outcome measures A price index of first line antiretroviral therapy with data on foreign assistance for HIV was used to estimate the associations of prices and foreign assistance with antiretroviral coverage (percentage of people with advanced HIV infection receiving antiretroviral therapy), controlling for national public health spending, HIV prevalence, governance, and fixed effects for countries and years. Results Between 2003 and 2008 the annual price of first line antiretroviral therapy decreased from $1177 (£733; €844) to $96 and foreign assistance for HIV per capita increased from $0.4 to $13.8. At an annual price of $100, a $10 decrease was associated with a 0.16% adjusted increase in coverage (95% confidence interval 0.11% to 0.20%; 0.19% unadjusted, 0.14% to 0.24%). Each additional $1 per capita in foreign assistance for HIV was associated with a 1.0% adjusted increase in coverage (0.7% to 1.2%; 1.4% unadjusted, 1.1% to 1.6%). If the annual price of antiretroviral therapy stayed at $100, foreign assistance would need to quadruple to $64 per capita to be associated with universal coverage. Government effectiveness and national public health expenditures were also positively associated with increasing coverage. Conclusions Reductions in price of antiretroviral drugs were important in broadening coverage of HIV treatment in Africa from 2003 to 2008, but their future role may be limited. Foreign assistance and national public health expenditures for HIV seem more important in expanding future coverage.